Mental health impairment and recovery after a road traffic injury: where do we stand in Europe? - Papadakaki, M.; Strukcinskiene, B.; Alves, T.; Lund, J. (Frontiers in Public Health, 2024)
Individuals sustaining road traffic injuries (RTIs) have been shown to run an increased risk of impaired mental health over time and delayed recovery. It is often the case that mental health symptoms get less clinical attention among individuals sustaining RTIs and therefore psychological support tends to be delayed. Effective management of these aspects in a clinical setting is still challenging in Europe due to health systems’ unpreparedness to predict the risk of poor mental health outcomes among survivors and appropriately intervene. Although a considerable amount of research is available in Australia, Canada and the US, the problem is still under-investigated in Europe. This paper reports on a review of the literature, which aims at identifying and presenting the latest research on the predisposing risk factors of poor mental health recovery among individuals sustaining an RTI in Europe. The review identified a huge mental health burden remaining long after the road traffic incident and a complex interplay of factors affecting mental health recovery after an RTI. Several challenges have been identified including the lack of a consistent definition for mental health recovery, the use of heterogeneous instruments and non-consistent epidemiological approaches and the lack of data collection mechanisms in Europe to capture the true impact of injuries. The paper concludes that existing efforts to fully understand the mental health outcomes of RTI patients remain inconsistent in Europe and offers evidence-based solutions to guide public health research and policy.